Strikes in Israël: The Histadrut in a Sectorial Perspective, 1965-1982 - Reshef, Yonatan; Fried, Yatzhak (Relations industrielles / Industrial Relations, 1986)
The paper presents a study ofstrike activity in Israël through a sectorial approach.